2019
DOI: 10.1002/jcb.29529
|View full text |Cite
|
Sign up to set email alerts
|

LIN28B/IRS1 axis is targeted by miR‐30a‐5p and promotes tumor growth in colorectal cancer

Abstract: Insulin receptor substrate 1 (IRS1) is a potential oncogene that has been implicated in several malignant tumors. However, the regulatory mechanism of IRS1 remains to be investigated. The aim of our current study is to unveil the mechanism by which IRS1 exerts functions in tumorigenesis of colorectal cancer (CRC). The expression level of IRS1 was found to be higher in CRC cells in comparison with the normal cell. To determine the role of IRS1 in regulating CRC cellular processes, loss‐of‐function assays were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…miR‐30a has been shown to play an inhibitory role in many cancers, such as cancers of the colon, breast, and lung 38‐40 . miR‐30a has also been previously reported to function as a tumor suppressor in PCa 12,13,15,16,41 .…”
Section: Discussionmentioning
confidence: 98%
“…miR‐30a has been shown to play an inhibitory role in many cancers, such as cancers of the colon, breast, and lung 38‐40 . miR‐30a has also been previously reported to function as a tumor suppressor in PCa 12,13,15,16,41 .…”
Section: Discussionmentioning
confidence: 98%
“…In this case, the miR-30 family, miR-504, miR-34c, miR-488, miR-15b, miR-195, miR-497, miR-15a, miR-503, miR-141, miR-182, miR-96, and miR-136 were also related to invasion, proliferation, metastasis and tumor growth, or survival of several cancers including CRC. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] However, there are few studies on the role of included prioritized miRNAs for interactions with obesity. For obesity there are some studies on mice, for instance, miR-16-5p decrease with high weight and a mutation in miR-16 gene lead to increasing in body weight.…”
Section: F I G U R Ementioning
confidence: 99%
“…More and more studies have shown that the aberrant versions of hsa-miR-30a-5p (miR-30a) are involved in the biological process of a variety of tumors. Some studies have shown that the Lin28b/IRS1 axis targeting miR-30a-5p promotes the growth of colorectal cancer (8). Liang et al (9) believes that plasma miR-30a-5p can be used as a biomarker for early diagnosis and prognosis of lung cancer.…”
Section: Introductionmentioning
confidence: 99%